Mental Capacity of Adult Patients in Health Care - Jeanette Hewitt (Handbook of the Philosophy of Medicine, 2015)
Mental capacity is a fundamental determinant of an individual’s ability to make autonomous decisions. Respect for autonomy is a legal and ethical requirement in healthcare provision, which necessitates that a person’s autonomous wishes be respected and informed consent validly obtained before therapeutic intervention is carried out. In Britain and many other Western jurisdictions, mental capacity legislation has developed with the aim of providing a framework for the assessment of mental capacity in health care, in a decision-specific context. Where a patient is judged to lack mental capacity with regard to a decision, the duty to respect autonomy is superseded by the duty to act beneficently and / or prevent harm which might otherwise occur due to the patient’s lack of capacity. Mental capacity legislation typically provides procedural criteria for assessing task-specific competence in terms of comprehension, appraisal and communication. Procedural criteria do not however specify a threshold for competency assessment, or provide guidance on evaluation of irrational belief systems. Procedural assessment of mental capacity may therefore provide only a partial indication of a person’s autonomy, and further evidence in terms of instrumental rationality may be necessary to evaluation of capacity.